Respuesta :

cher
Equation 1)  y = -2x - 6
Equation 2)  y = x + 9

Move equations around, by moving the (x)s to the left side of the equation so that x and y are on the same side.

To do so, add 2x to both sides in equation 1, and subtract x from both sides in equation 2.

1)  2x + y = 6
2)  -x + y = 9

Subtract equations from each other.

3x = -3

Divide both sides by 3.

x = -1

Plug in -1 for x in first equation.

y = -2x - 6

y = -2(-1) - 6

Simplify.

y = 2 - 6

y = -4

(-1, -4)  ==> x = -1, y = -4

~Hope I helped!~
y = -2x - 6
y = x + 9

So like all you gotta do it move the Xs onto the same side as the Ys are on.

When doing that type of stuff though, you gotta change their signs from positive to negative, or negative to positive.

2x + y = -6
-x + y = 9

Just subtract the equations.

3x = -15

Divide both of the sides by 3.

x = -15/3

Simplify.

x = -5

Plug in the x value (-5) into one of the equations.

2x + y = 6

2(-5) + y = 6

Simplify.

-10 + y = 6

Add 10 to both sides so that y is all by itself man.

y = 6 + 10

Simplify .

y = 16

ANSWER : X = -5 AND Y = 16

:-)
ACCESS MORE